IMPROVING ORGANIZATIONAL PERFORMANCE THROUGH ENVIRONMENTAL PASSION AND ENVIRONMENTAL PERFORMANCE - Adi, Susilo; Wardi, Agustinus (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Purposes: This study aims to develop an empirical research model in improving organizational performance. The conceptual model is proposed based on Green Human Resource Management, Environmental Passion and Environmental Performance. Research Methodology: Using 200 respondents in the manufacturing industry in Central Java, the model was tested to obtain research data, the data were analyzed using inferential statistical data analysis using regression techniques and AMOS software 25. Result: The results showed that all proposed concepts were acceptable and the model proposed is quite feasible to be developed in improving organizational performance. Limitations: The limitations of this study are still using concepts that are abstract in nature and have not been able to provide specific dimensions for analysis with respect to endogenous variables, namely organizational performance. Contribution: In this study, this research develops new concepts related to concepts from stakeholder theory, other atomic theories and operations management theories. The result of this research contributes as recommendations for practitioners in improving organizational performance referring to environmental performance and the concept of sustainability in the field of management.